Prevalence and risk of malaria, anemia and malnutrition among children in IDPs camp in Edo State, Nigeria - Oluwaremilekun G. Ajakaye; Mojirayo R. Ibukunoluwa (Parasite Epidemiology and Control, 2020)
Background: Malaria, anemia and malnutrition are global health challenges with significant morbidity and mortality, with higher rates among children particularly in Africa. Recently there has been displacement of over a million people due to different crisis in Nigeria. However, there is limited study on the public health issues facing these vulnerable populations. This study evaluated the prevalence and risk factors for malaria infection, anemia and malnutrition among children living in internally displaced persons (IDP) camp in Edo state, Nigeria. Method: A total of 250 children up to 10 years old were included in the study in the year 2018. Malaria infection was confirmed by rapid diagnostic tests. The hematocrit level was obtained using a centrifuge microhaematocrit and converted to haemoglobin using standard conversion while nutritional status was determined from anthropometric measurements collected, and demographic characteristics were obtained by the use of questionnaire. Anemia and malnutrition were defined according to World Health Organization standards. The logistic regression analysis was used to determine associations between predictor variables and primary outcomes. Result: Malaria infection and anemia were recorded for 55.2% and 54.0% of the children, respectively while malnutrition prevalence was 41.2% with wasting, underweight and stunting occurring in 0.04%, 11.2% and 39.2% respectively. Age was a significant risk factor for malaria with higher odds of having malaria infection in children 6–10 years of age [odds ratio (OR) = 2.032, P = 0.021] than in younger children. Being 6–10 years (OR = 2.307, P = 0.015) and having malaria infection (OR = 1.693, P = 0.048) were identified as significant risk factors of anemia while being in the age group of up to 5 years was the only significant risk factor (OR for the older age group = 0.251, P ≤ 0.001) associated with malnutrition. Specific attention needs to be paid to children in IDP camps. Conclusion: Anemia and malnutrition control should be integrated with existing malaria control and should include children above five years of age. Keywords: Malaria, Anemia, Malnutrition, Children, IDPs, Nigeria